Orlistat exerts anti-obesity and anti-tumorigenic effects in a transgenic mouse model of endometrial cancer - Xu, Guangxu; Zhao, Ziyi; Wysham, Weiya Z.; Roque, Dario R.; Fang, Ziwei; Sun, Wenchuan; Yin, Yajie; Deng, Boer; Shen, Xiaochang; Zhou, Chunxiao; Bae-Jump, Victoria (Frontiers in Oncology, 2023)
Among all cancers, endometrial cancer is most strongly associated with obesity, with more than 65% of endometrial cancers attributable to obesity and being overweight. Fatty acid synthase (FAS), a key lipogenic enzyme, is expressed in endometrial cancer tumors and is associated with a worse prognosis for this disease. Orlistat, an FAS inhibitor, is an FDA-approved weight loss medication that has demonstrated anti-tumor activity in a variety of preclinical cancer models. In this study, the Lkb1fl/flp53fl/fl mouse model of endometroid endometrial cancer was exposed to three diet interventions, including a high fat diet (obese), a low fat diet (lean) and switch from a high fat to a low fat diet, and then exposed to orlistat or placebo. The mice fed a high-fat diet had significantly increased body weight and tumor weight compared to mice fed a low-fat diet. Switching from a high-fat diet to a low fat diet led to a reduction in mouse weight and suppressed tumor growth, as compared to both the high fat diet and low fat diet groups. Orlistat effectively decreased body weight in obese mice and inhibited tumor growth in obese, lean, and the high fat diet switch to low fat diet mouse groups through induction of apoptosis. Orlistat also showed anti-proliferative activity in nine of 11 primary cultures of human endometrial cancer. Our findings provide strong evidence that dietary intervention and orlistat have anti-tumor activity in vivo and supports further investigation of orlistat in combination with dietary interventions for the prevention and treatment of endometrial cancer.